Numerical simulation of single point diamond turning - Teoh, Yeong Chia (2009)
A coupled thermo-mechanical plane-strain large-deformation orthogonal cutting finite element model is presented in this thesis by using the ABAQUS finite element code to simulate the cutting mechanics of OFHC Copper in Single-Point Diamond Turning (SPDT). The simulations concern the study of stress and strain imparted in the workpiece during metal cutting process. Round edge cutting tool is used in this study since the tool edge radius has comparable size to the uncut chip thickness in SPDT. The tool is treated as perfectly rigid body where the cutting conditions and boundary conditions are prescribed at a reference point. Workpiece material is modeled as thermo-visco-plastic material that is considered dependent upon the plastic strain, the plastic strain rate and temperature variations. The flow stress calculation is expressed as the form of Johnson–Cook’s constitutive equation that take into account the effect of the large strain, strain-rate and temperature associated with cutting on the material properties. To reduce computational time and cost, the workpiece is discretized by nonuniform mesh. Mesh distortion problem due to large deformation in front of tool tip during cutting simulation is solved using pure deformation technique. A more realistic and physically based chip formation can be achieved by using this method. Chip formation yield from the finite element method simulation of OFHC Copper is observed and it revealed good chip morphology that agrees well with the previous studies. The model is validated with the published report based on Von Mises Stress and found to be in good agreement also. This model is useful to economically analyze SPDT and thus to meet the need for improve productivity and quality of machining operations in SPDT.